Warm-up in anderen Sportarten - Klenner, D.; Herrmann, J.; Hädrich-Hörmann, E.; Krop, M.; Franke, B. (Leichtathletiktraining, 2023)
Trainer verschiedener Sportarten berichten, wie sie das Aufwärmen gestalten.